PENGARUH TINGKAT KEPATUHAN WAJIB PAJAK, PENGETAHUAN PAJAK, DAN SYSTEM E-FILING TERHADAP PENERIMAAN PAJAK PADA KPP PRATAMA TAMPAN PEKANBARU - Yogi Maihendra; Zul Azmi; R. Septian Armel (UIR Press, 2024)
This research aims to test the influence of the level of taxpayer compliance on tax revenue at KPP Pratama Pekanbaru Tampan, to test the influence of tax knowledge on tax revenue at KPP Pratama Pekanbaru Tampan. Test the effect of the e-filing system on tax revenue at KPP Pratama Pekanbaru Tampan. This research method is quantitative research, namely research using numbers as a measuring tool to measure a research object. The results of this research show that the level of taxpayer compliance (X1) has a positive effect on the tax revenue variable. This means that the more taxpayers comply with their tax obligations, the more tax revenues will increase. Tax knowledge (X2) has a positive effect on the tax revenue variable. This means that the higher the tax knowledge, the more orderly the tax reporting will be and the tax revenue will increase. The e-filing system has a positive effect on the tax revenue variable. This means that the easier it is for taxpayers to use the e-filing system, the more they will comply with reporting and paying taxes so that tax revenues will increase.